Pengaruh Pengalaman Diklat dan Motivasi Mengajar Terhadap Penguasaan Materi PAI di SD Negeri se-Kecamatan Kota Masohi Kabupaten Maluku Tengah - Ani Rehan Sopaheluwakan (Peneliti.net, 2019)
This study aims to find out: The effect of training experience and teaching motivation on mastery of the material of teacher Islamic Education in Public Elementary Schools in Kota Masohi District. This research is classified into quantitative research. The population of this study amounted to 39 people. Furthermore, the entire population is determined as a sample. The data collection instrument used consisted of tests for the mastery variables of PAI material, questionnaires for teaching motivation variables and documents for training experience variables. The data analysis technique used is descriptive and inferential analysis. The results of this study indicate that the path coefficient value X1 to Y = 1,000, and the results of significant test path coefficients obtained tcount = 8.803 and ttable = 2.028 at the significance level α = 0.05 with free degrees (db) = 36 Because the value of tarithmetic = 8.803> ttable = 2.028, it is concluded that the path coefficient X1 to Y is significant. This finding provides information that mastery of teacher Islamic religious education material is directly influenced positively by the training experience followed by the teacher. The calculation of the path coefficient value X2 to Y is obtained by the value = 0.252. Based on the results of the calculation of the significance of the path coefficient obtained tcount = 2.216 and ttable = 2.028 at the significance level α = 0.05 with free degrees (db) = 36. Because the value of tarithmetic = 2.216> ttable = 2.028 then concluded that the path coefficient X2 to Y is significant. This finding provides information that mastery of Islamic Religious Education material is directly influenced positively by teacher teaching motivation. Based on the results of the calculation of the path coefficient value X1 to X2 obtained a value of = 0.534 and the results of significant test calculations the path coefficient is obtained by tcount = 4.890 and the value of ttable = 2.026 at the significance level α = 0.05 with free degrees (db) = 37. Because the value of tcount = 4.890> ttable = 2.026, it is concluded that the path coefficient X1 to X2 is significant. This finding provides information that the teaching motivation of PAI teachers is directly influenced by the training experience followed by the teacher. In other words, the more often the teacher follows the training, the higher the motivation to teach his Islamic Religious Education teacher